2008
DOI: 10.21101/cejph.a3454
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Antibodies to Varicella-zoster Virus in Madrid (Spain) in the Absence of Vaccination

Abstract: Objective: to ascertain the seroprevalence of antibodies to varicella-zoster virus in the Madrid population prior to the introduction of vaccination. Study design: Cross-sectional antibody seroprevalence study. Methods: Population: persons aged 2 to 40 years in Madrid. Field work: September 1999 to April 2000. Data were collected on demographic and socioeconomic variables and on a number of exposures. IgG antibodies were determined using Enzyme Linked ImmunoSorbent Assay (ELISA), and antibody prevalence broken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…Sampling was done as described for the third Survey [Pérez-Farinós et al, 2008], but including people aged 41-60 years. Serum samples were collected from January to May 2008.…”
Section: Samples and Methodsmentioning
confidence: 99%
“…Sampling was done as described for the third Survey [Pérez-Farinós et al, 2008], but including people aged 41-60 years. Serum samples were collected from January to May 2008.…”
Section: Samples and Methodsmentioning
confidence: 99%
“…Seroprevalence studies demonstrated varicella specific antibodies in more than 90% of ten-year-olds (19). During the prevaccine period, the majority of varicella cases were in children and primary school students seen by paediatricians and school physicians.…”
Section: Discussionmentioning
confidence: 99%
“…Patients are given two doses of the live attenuated varicella vaccine (Varivax©, Merck and Company, Inc, West Point, PA) according to the recommended schedule of the American Academy of Pediatrics (23). Studies have reported the presence of IgG antibodies to VZV in healthy (non-vaccinated) children (24,25) and antibodies against VZV and rubella virus (26), in the absence of vaccination. VZV seroprevalence was highest in these children at 48 and 60 months old (25).…”
Section: Discussionmentioning
confidence: 99%